The Creativity of the PAI Klaten Teacher Community in Utilizing Belajar.id Accounts - Gunagraha, Shindid; Pramono, Aji Joko Budi (Al-Ulum: Jurnal Pendidikan Islam, 2025)
The purpose of this research is to reveal how the creativity of the PAI teacher community in Klaten Regency in utilizing belajar.id accounts as a space for educational digitalization. This research method uses qualitative field research with the research subject being the PAI teacher community at the junior high school level in Klaten Regency. The results of the study show that PAI teachers utilize belajar.id accounts with various creativity through digital platforms such as Canva, Quiziz, and Google Classroom, this form of utilization not only increases students' interest and understanding but encourages them to produce digital works that are integrated with Islamic values.